Evaluasi Status Hara Tanah Berdasarkan Posisi Lahan di Kebun Inti Tanaman Gambir (Uncaria gambir Roxb.) Kabupaten Pakpak Bharat - Muhammad Arif Setiawan; Abdul Rauf; Benny Hidayat (Universitas Sumatera Utara, 2014)
Evaluation of soil nutrient status is one way to be able to determine the nutrient needs of the soiland the management techniques that will be performed on an area of land. This study aimed toevaluate the nutrient status of the soil (pH, N, P, K, Ca, Mg) based on the position of the land in thecore Gambir Garden Pakpak Bharat District. It was conducted at the core Gambir Garden PakpakBharat District, North Sumatra on March 2013 until June 2013. The method used in this research isdescriptive method by conducting surveys and soil sampling based on the position of the land whichis on the top of the hill, hillside and valley side. The results showed soil nutrient status of N in CorePlant Gambir Garden Pakpak Bharat District. is likely to increase in the valley compared to the topof the hill and hillside. As for the value of pH and P are highly the same, while the value of K, Caand Mg rate tends to decrease.Keyword: land position, soil nutrients, gambir (Uncaria gambir Roxb.)